Effects of visual complexity and ambiguity of verbal instructions on target identification. Issue 2 (17th February 2019) - van Marlen, Tim; van Wermeskerken, Margot; van Gog, Tamara
ABSTRACT: Research has shown that visual complexity and the ambiguity of verbal information affect the speed and accuracy of locating targets during visual search. The higher the visual complexity and description ambiguity, the slower and poorer the target identification performance. Because these factors are seldom studied in combination (even though they regularly co-occur), it is unclear whether they would interact. Therefore, in two experiments, participants viewed images that displayed cartoon-like characters and had to correctly identify a character from a verbal description under conditions of low/high visual complexity and low/high description ambiguity (manipulated within-subjects). Results revealed that high ambiguity descriptions resulted in lower accuracy and slower response times. However, our manipulation of visual complexity did not affect performance or response times either in itself or in interaction with verbal ambiguity. Findings are discussed in terms of theoretical and practical implications, for instance, for multimedia learning.